Mandarin translation and validation of the Theory of Mind Inventory‐2 and the Theory of Mind Task Battery for autistic children in Mainland China. - Tian, Mi; Au, Rachel H. Y.; Cao, Shiyue; Shi, Huiming; Xin, Cong; Xia, Wenyu (British Journal of Developmental Psychology, 2026)
The objective of the study was to translate and culturally adapt two important measures of theory of mind (ToM)—the Theory of Mind Inventory‐2 (ToMI‐2) and the Theory of Mind Task Battery (ToMTB)—into a Mandarin version (the ToMI‐2‐M and the ToMTB‐M). The ToMI‐2‐M and the ToMTB‐M were first developed through translation, expert validation, and a pilot study. Ninety‐four autistic children and 43 verbal ability‐matched non‐autistic children (aged 2.5–8 years) were then tested to evaluate the psychometric properties of the two assessment tools. Both the ToMI‐2‐M and the ToMTB‐M showed good internal consistency and test–retest reliability. Content validity was supported by an expert panel. Concurrent validity was supported by the two assessment tools' correlations with other ToM tasks, visual perspective taking, inhibitory control, and autistic characteristics. The discriminative validity was demonstrated by significantly higher scores of non‐autistic children than autistic children on these assessment tasks. Age‐related changes and the receiver operating characteristic curve analysis also provided support. The ToMI‐2‐M and the ToMTB‐M showed good psychometric properties and represent useful tools for assessing ToM abilities of autistic children and non‐autistic children.